A Solid in Disguise: Structure Determinations, Polymorphism, and Thermal Behavior of the Silyborane pinB‐SiMe2Ph. Issue 21 (2nd August 2018) - Kleeberg, Christian; Plotzitzka, Jacqueline
Abstract : The silylborane pinB‐SiMe2 Ph (1 ) [pin = (OC(Me)2 C(Me)2 O)], an established reagent in various silylation and borylation reactions, was studied in detail with respect to its solid‐state structure. In contrast to the common understanding, 1 is a solid at ambient temperature. However, crystallization is strongly hampered and not observed above –18 °C. Single crystal X‐ray diffraction studies on 1 furnish two distinct structurally complex polymorphs. Polymorph 1A crystallizes in a triclinic space group, P 1, with two pairs of independent molecules in the asymmetric unit ( Z = 8, Z ′ = 4). The second polymorph, 1B, in an orthorhombic space group Fdd 2 comprises three independent molecules ( Z = 48, Z ′ = 3). Within both polymorphs as well as between the polymorphs the individual molecules of 1 exhibit only subtle conformational differences, with respect to the orientation of the Bpin and the phenyl group. Abstract :